Application Of Self-Directed Problem-Based Learning To Improve Higher Order Thinking Skills In Vocational Education - Siti Nur Hidayah (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
21st-century Learning provides profound changes in the learning process in school because students must control their Learning to increase their critical thinking and problem-solving skills. The statement above, in line with Malcolm Knowles's research results, states that Self-directed Learning can improve students' critical thinking through intuition and analysis experience. The problem is that in vocational education, students emphasize hard skills and practice. Learning 21st-century demands that students have soft competency to influence how they think in making decisions. Therefore, the researcher aims to determine the effect of the self-directed learning model on the students' higher-order thinking Skills in Vocational Education. The method used in this research is quantitative, using two groups, namely the experimental class and the control group, with 34 students in each class. Class Experiments get treatment of self-directed Problem-based Learning that has been developed, while the control class did not get this treatment. This learning model is applied to the Mechanics Technique Subject; then, the post-test learning outcomes are independent sample t-tested using SPSS to determine the significant effect on higher-order thinking skills in the transfer knowledge aspect. This study found that Self-directed Problem-based Learning positively impacts Higher-order Thinking Skills in Vocational Education, which can be seen from the t-test results more than t-table (3.807>1.668).